?GC ANALYSIS OF CHLORINATED CATECHOLS IN SOILS BY INTERNAL STANDARD METHOD (Biological Sciences - PJSIR, 1994)
An improved gas chromatography (GC) analysis method, was developed with seven chlorinated catechol com- pounds in soils. Six solvent systems were tested by a shaking method of extraction. The method include extraction, mixing with internal standard 2,6·dimethoxyphenol, then derivatization with pentafluorobenzyl bromide, cleanup by water-toluene shaking and then injected to Gc. The recovery yields varied largely from 67 to 90% within six solvent sys- tems. Two solvent system: Diethykther-hexane-acetoneheptane (3:3:2:2:) and hexane-heptane-chloroform (1:1:1:) gave the highest yields in both soils. The standard deviations and t-test were applied to the results where some significant variations were also recorded.